The inflationary process in Argentina, 1943-60 - Villanueva, Javier; United States (Buenos Aires : Distributed by Editorial del Instituto Torcuato di Tella, 1966)
This present work is a study of the behavior of prices, wages, profit margins of food distribution industries and the terms of trade in Argentina during the years 1943 to 1960.
Bibliography: p. 153-164. Bibliographical footnotes.
osa;20/09/18
Loans
Keywords: Inflation (Finance)